Trade Facilitation and Economic Development : New Approach to Quantifying the Impact - Wilson, John S. (Washington, DC: World Bank, 2014)
This article analyzes the relationship between trade facilitation and trade flows in the Asia Pacific region. Country specific data for port efficiency, customs environment, regulatory environment, and e-business usage are used to construct indicators for measuring trade facilitation. The relationship between these indicators and trade flows is estimated using a gravity model that includes tariffs and other standard variables. Enhanced port efficiency has a large and positive effect on trade flows. Regulatory barriers deter trade. Improvements in customs and greater e-business use significantly expand trade but to a lesser degree than improvements in ports or regulations. The benefits of specific trade facilitation efforts are estimated by quantifying differential improvements in these four areas among members of the Asia Pacific Economic Cooperation (APEC). A scenario in which APEC members with below-average indicators improve capacity halfway to the average forall members shows that intra-APEC trade could increase by Dollar 254 billion, or 21 percent of intra-APEC trade flows.